Repliek - Fijnaut, C. (BMGN - Low Countries Historical Review, 2008)
ResponseIt is good for the further development of historical research into the police force that the reviews not only extol the virtues of the study in question, but also ask pertinent questions about the basic principles behind the research, the way in which the subject was methodically examined, and how the findings were edited. The question in the critique written by Van Doorslaer concerning the magistrature’s role in how the Dutch police operated during the German Occupation, is a matter that certainly deserves more attention than it received in this study. However, anyone wishing to give an informed answer to this question would not only have to scrutinize the relationship between the magistrates and the police, but would also have to closely examine the relationship between the government and the police as well. This is because in the Netherlands the government traditionally has a lot to say with regard to the police. The question, therefore, is how did both of these institutions function towards the police during the German Occupation. The core question in the comments made by Jansen is whether enough attention was given to the position of the police in the constitutional state. He is of the opinion that the problematic matter of police authority was inadequately dealt with. Indeed, this issue was largely bypassed, although this was not the case with regard to the position of the police in the constitutional state. Its relationship with government and the legal system, in other words, how the police force is embedded within the state system, is traditionally seen as one of the key questions in this context. Spierenburg argues in his critique that the politicalorganisational developments are dealt with in too biased a fashion in this study and so the professional developments in the police machinery and the changes in the monopoly on the use of force are skirted over. This statement cuts no ice for a variety of reasons. The main one is that the changes in the monopoly on the use of force and in the police profession take shape, first and foremost, in the organisational development of the police. This link between them is continuously and rigourously examined in this study. This review is part of the discussion forum 'De geschiedenis van de Nederlandse politie' (Cyrille Fijnaut).